Assessment of Pb, Cd, As and Hg concentration in edible parts of broiler in major metropolitan cities of Tamil Nadu, India. (2021) - M, Mathaiyan; A, Natarajan; Rajarathinam, Xavier; S, Rajeshkumar
Graphical abstract: Possible contaminant route of heavy metals in human through chicken consumption. Highlights: Pb exceeded maximum residue limit in meat and liver in all 5 cities of Tamil Nadu state of India while kidney and neck samples of Chennai alone exceeded maximum residue limit. As was found to be exceeding maximum residue limit in breast (0.1 mg/kg) and liver (0.5 mg/kg) samples in many metropolitans of Tamil Nadu state. Cd and Hg concentration was within the maximum residue limit in all metropolitan samples. Daily dietary consumption of Pb, Cd, As and Hg from edible parts of chicken in Tamil Nadu metropolitans was well within the permitted quantity. Abstract: The risk of heavy metals contamination in meat and meat products is of great concern for both food safety and from human health point of view. The present study was carried out to assess the heavy metal residues such as Pb, Cd, As and Hg in broiler chicken meat, neck and edible organs (liver and kidney). In the present study, 150 samples were randomly collected from major cities (Chennai, Coimbatore, Madurai, Trichy, and Salem) of Tamil Nadu state, India and analyzed for Pb, Cd, As and Hg residues (mg/kg) using inductively coupled plasma-mass spectrometry (ICP-MS) technique. The results revealed that lead (Pb) concentration was higher in meat and liver samples of all cities and the highest concentration was detected in Chennai followed by Coimbatore, whereas in kidney and neck samples, Chennai metropolitan alone exceeded the MRL value of 0.5 and 0.1 mg/kg respectively. The residues of cadmium and mercury in meat and meat samples were within the permissible limit in all the metropolitans. Arsenic was found exceeding the MRL of 0.1 mg/kg in the breast samples of all the metropolitans (0.2141–2.2285 mg/kg, the highest being in Trichy), except for Madurai, which recorded very low value (0.0239 mg/kg). Arsenic was found in the range of 0.1110–1.0850 mg/kg in liver samples thus exceeding MRL value. Neck and kidney samples did not contain any Arsenic. Thus it can be concluded that the lead concentration in meat and edible organ samples collected from all the metropolitans exceeded the MRL values and is an indication of contamination. Appropriate precautions are warranted to minimize the heavy metal consumption contamination especially of Pb and As.